Towards the development of an electrochemical immunosensor for the identification of transient ischemic attack via the labeless detection of biomedical markers. - Barton, Andrew Charles (Cranfield University, 2006)
The thesis describes the development of generic platforms for labeless transduction of binding events. A particular application of the project is the labeless detection of biochemical markers for stroke, specifically transient ischemic attack, to facilitate rapid diagnosis and subsequent introduction of appropriate therapy within the required three-hour time frame. Novel biocomponents are under development for detection of these biochemical markers, and further demonstration of the generic nature of the technologies being developed will be realised via the use of a library of monoclonal antibodies as capture biocomponents. This work forms part of an investigation into labeless affinity immunosensor detection via impedimetric transduction utilising the technique of electrochemical impedance spectroscopy (EIS). Novel microelectrode arrays were fabricated by the sonochemical ablation of a homogeneous insulating layer of poly(o-phenylenediamine) exposing discrete areas of an underlying screen-printed conductive substrate. The receptor biocomponents are then subsequently coupled to the transducer by either electropolymerised entrapment or non-covalent affinity within and/or at the surface of conducting polymer ‘mushroom’ shaped protrusions for site-specific immobilisation. Upon exposure to a range of concentrations of antigen analyte solution, complex plane impedance analyses are used to relate the differing redox states of the polymer to possible charge transfer and / or related mechanisms between the immobilised antibody / antigen analyte and the polymer. Results show that signal differentiations were obtained, for a number of antibody / antigen species over a range of concentrations of clinical relevance (ng-pg/mf1), suggesting that the techniques employed offer a viable approach towards the labeless quantification of biochemical markers of transient ischemic attack (TIA).